Clinical And Genetic Study of The Sptlc1 Gene Mutation in Patients With Heridetary Sensory Neuropahty Type 1 - H, Mourad; W, Fadel; M, El Batch (IIUM Medical Journal Malaysia, 2009)
Introduction: Hereditary sensory neuropathy type 1 (HSN1) is the most common hereditary disorder of peripheral sensory neurons. Materials and methods: This study was carried out on 15 patients with hereditary sensory neuropathy type-1 and 10 healthy individuals as a control group. Detailed family history and thorough clinical and neurological examination were performed to all patients. Nerve conduction velocity of ulnar and lateral popliteal nerves (motor and sensory) as well as audiograms was carried out for all members of the studied groups. The laboratory study included the determination of serum C-reactive protein (CRP) and serum nucleasomes as well as molecular detection of the serine palmitoytransferase (SPTLC-1) gene mutations for all studied groups. Results: There was predominance in male who developed more sever clinical manifestations than females. The disease onset was in the second and third decades of life. Patients with HSN 1 manifested reduced conduction velocity in both motor and sensory fibers of the lateral popliteal nerve (p< 0.01) however the ulnar nerve was spared (p = 0.61). Audiometry revealed bilateral partial nerve deafness in 3 cases and complete deafness in one case. Serum CRP and nucleosomes were significantly elevated in all patients as compared to the control group (p < 0.01). The genetic study revealed mutations of the SPTLC1 in all studied patients compared to the control group. Point mutation C133W was observed in younger patients having severe clinical manifestations with prominent leg ulceration, while the point mutation C133Y was observed in the older patients complaining of hearing loss. The mutation V144D was found in patients with mild clinical presentation having minimal ulceration and no hearing abnormalities. Conclusion: The SPTLC1 gene mutations play an important role in the pathogenesis and variability in clinical presentation of HSN1 disease.